EVALUASI KINERJA IRIGASI DAN PRIORITAS PEMELIHARAAN DAERAH IRIGASI UNIT PELAKSANA TEKNIS (UPT) III KABUPATEN DELI SERDANG - Nuriaman; Yuzni, Siti; Wijaya, Kinanti (Universitas Negeri Medan, 2024)
The Irrigation Area located in the Technical Implementation Unit (UPT) III of Deli Serdang Regency has an area of 1,042 Ha with 9 Irrigation Areas. Evaluation of the irrigation performance index is carried out to maintain the functional ability and sustainable management of an irrigation system. Evaluation of irrigation performance assessment using Minister of Public Works and Public Housing Regulation Number 12/PRT/M/2015 concerning Exploitation and Maintenance of Irrigation Networks. The research was carried out using the method of collecting data on the condition of the irrigation network, then continued with the analysis of questionnaire data regarding priorities for selecting irrigation area maintenance from selected respondents to obtain values for the degree of importance between criteria and between alternatives. From the irrigation performance index assessment data, a weight value of 60.30% was obtained, which means the performance index is low so attention and handling are needed. Data analysis using the Analytic Hierarchy Process (AHP) method with a hierarchical structure, followed by calculating the weights of criteria and alternatives using Super Decision software, resulted in the priority scale for handling the maintenance of the UPT III irrigation area of Deli Serdang Regency, namely the priority is the Kotasan irrigation area and the second Sei Tuan irrigation area.